Pengembangan Multimedia Interaktif Berbasis TPACK pada Mata Pelajaran Informatika Kelas VII di SMP - Anisya, Anisya; Anugrah, Septriyan; Hendri, Nofri; Masnur, Alkadri (Indo-MathEdu Intellectuals Journal, 2024)
The research aims to develop framework-based interactive multimedia on Techonogical Pedagogical Content Knowledge in informatics subjects at the junior high school level. The type of research used is the Research and Development (R&D) method with a development model (Analysis, Design, Development, Implementation, Evaluation). At the development stage, an analysis of needs in the field, storyboard design, media development using the articulate storyline application, and product trials were carried out to students. The instruments used in the study consist of observations, questionnaires, and learning outcome tests with the aim of determining the practicality and effectiveness of the products developed. The validation test data from the material aspect obtained a score of 4.00 with the criterion of "Strongly Agree". Meanwhile, in terms of media tested by two media validators, the average score from validator 1 was 3.85 with the "Valid" category and from media expert 2 was 4.74 with the "Very Valid" category. The results of the practicality test were obtained with a score of 4,210 in the category "Very Practical". The results of the effectiveness test obtained an average N-gain score of 71.24% which is included in the category of "Quite Effective". Based on the assessment that has been obtained, the TPACK-based interactive multimedia developed is very feasible and effective to be used in learning activities